Union voices: tactics and tensions in UK organizing - Simms, Melanie; Holgate, Jane; Heery, Edmund (Ithaca, NY., 2012)
"In Union Voices, the result of a thirteen-year research project, three industrial relations scholars evaluate how labor unions fared in the political and institutional context created by Great Britain's New Labour government, which was in power from 1997 to 2010. Drawing on extensive empirical evidence, Melanie Simms, Jane Holgate, and Edmund Heery present a multilevel analysis of what organizing means in the UK, how it emerged, and what its impact has been.